Trace Detection of Metalloporphyrin-Based Coordination Polymer Particles via Modified Surface-Enhanced Raman Scattering Assisted by Surface Metallization - Yu Sun; Alessio Caravella (International Journal of Analytical Chemistry)
This study proposed a facile method to detect metalloporphyrin-based coordination polymer particles (Z-CPPs) in aqueous solution by modified surface-enhanced Raman scattering (SERS). The SERS-active particles are photodeposited on the surface of Z-CPPs, offering an enhanced Raman signal for the trace detection of Z-CPPs.